Dry Eyes Post Laser Assisted in Situ Keratomileusis - Ni Komang Miraditi (Rifa'Institute, 2021)
Dry eye is one of the most common complications following laser-assisted in situ keratomileusis (LASIK), with nearly all patients experiencing some degree of postoperative dry eye symptoms. Postoperative dry eye affects approximately 50% of patients at 1 week postoperatively, 40% at 1 month, and 20%-40% at 6 months postoperatively. LASIK can cause intracorneal nerve damage, goblet cell damage caused by suction, and can cause changes in the shape of the central cornea. Dry eye diagnosis can be made using a questionnaire to determine the patient's history, examination of tear break up time, staining of the eye surface using fluorescein or lissamine green, and Schirmer's test. This reserech use Literatur Review Method. Post-LASIK dry eye complaints such as irritation, red eyes, foreign body sensation, pain, gritty, and photophobia. Management of post-LASIK dry eyes can be done by giving tear supplements, anti-inflammatory agents, ointments and eye patches, and treatment of meibomian gland dysfunction. Post-LASIK dry eye usually peaks within a few months after surgery, and then improves in most patients 6-12 months after surgery. Although dry eye signs and symptoms are most common in the immediate postoperative period and are usually only temporary, a minority of individuals experience chronic and severe dry eye